Valorization of palm oil via cross-metathesis reaction using 1-octene - M., Thangavel; S. Y., Chin (Taylor & Francis, 2022)
The use of palm oil-derived polyol in polyurethane manufacturing is restricted owing to its poor hydroxyl value, which results in a suboptimal polyurethane network. Palm oil could be first chemically modified by cross metathesis (CM) into olefin and ester products with terminal double bonds prior to converting it to the polyols with optimum hydroxyl value. Due to the catalyst degradation and the unwanted self-metathesis reaction, the plant oil CM employing ethylene has been limited by its poor selectivity and low yield. The goal of present research is to investigate the palm oil CM using 1-octene from the aspects of parametric and kinetic analysis. The use of 1-octene was hypothesized to prevent the formation of undesired catalytic intermediates and hence allowing the ruthenium-based Hoveyda Grubbs second generation catalyst (2nd HGC) to maintain its activity and stability. Adopting one factorial at time (OFAT) in a batch system, the effect of different parameters on cross-metathesis of palm oil was examined. The variation in reaction time, temperature, reactant molar ratio of 1-octene to triolein (MOC/TR), and catalyst loadings were correlated to triolein conversion, yield, and selectivity of 1-decene. The products such as 1-decene and glyceryl tri-9-decenoate were quantified using Gas Chromatography-Mass Spectrometry (GC-MS). The maximum triolein conversion and 1-decene yield, 97.78% and 293.36% respectively, were obtained when the cross metathesis of palm oil using 1-octene occurred at 343 K for 2 h with MOC/TR of 8 and catalyst loading of 5 ppm. After three consecutive catalytic tests carried out at best operating condition, the insignificant decline in the reaction performance evidenced that the 2nd HGC catalyst remained active and stable. It was also found that the power-law model well predicted the concentration profile of the cross-metathesis of palm oil using 1-octene, estimating activation energy of 22583 J/mol. This study developed a new technically feasible process for adding value to palm oil, by enabling the use of palm oil as a feedstock for the production of polyol.